Governing risk : the imf and global financial crises - Moschella, Manuela ([S.l.] : Palgrave Macmillan, 2012)
By comparing the policies the international community requested the IMF to follow in the aftermath of the Mexican, Asian and subprime crises, the book traces the evolution of the international regulatory framework from an agent-centered constructivist perspective.